The criteria of healthy humans from the perspective of religious texts - Mahdi Fani; Morteza Abdoljabbari; Foroozan Atashzadeh-Shoorideh; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: The Holy Quran contains a lot of subjects on human health. In addition to physical health, the Quran considers mental health as another important dimension to human health. The current study aimed at identifying the criteria for recognizing a healthy human from the perspective of religious texts. In this regard, attempts were made to detect the criteria for identifying a healthy human from an Islamic viewpoint. To this end, ideas proposed by a number of religious figures, including Imam Khomeini, the Supreme Leader, and martyr Motahhari, were investigated. Method: In this descriptive study, content analysis was used to examine verses of Quran and religious experts' interpretations of these verses about human health. Additionally, the narratives related to the Quran-based interpretations of Prophet Mohammed's Ahl al-Bayt, especially about the spiritual dimension of human health, were investigated. Furthermore, contemporary domain experts' opinions were sought to confirm the extracted criteria. All ethical issues were observed in this study and the authors declared no conflict of interests. Results: Based on the obtained results, a human can be regarded as healthy in two dimensions: materialistic and spiritual. It should be noted that these two are not interdependent. In other words, a human may be physically healthy, but spiritually unhealthy. On the contrary, a person may be spiritually healthy, but physically unhealthy. Spiritual health plays a more significant role in human happiness. Conclusion: As argued by domain experts, humanity has to do with people's spiritual aspect rather than their physical and materialistic one. Spiritual health is more important than physical health. Spiritual diseases are more significant than physical ones. Imam Ali (peace be upon him) says, 'the piety of heart is superior to physical health.' Therefore, a human is regarded as healthy in two dimensions. The subject of materialistic health falls within the domain of medicine, while the topic of spiritual health is categorized within the realm of religion. For downloading the full-text of this article please click here.